A new selenium source from Se-enriched Cardamine violifolia improves growth performance, anti-oxidative capacity and meat quality in broilers - Xu, Xiao; Wei, Yu; Zhang, Yue; Jing, Xiaoqing; Cong, Xin; Gao, Qingyu; Cheng, Shuiyuan; Zhu, Zhenzhou; Zhu, Huiling; Zhao, Jiangchao; Liu, Yulan (Frontiers in Nutrition, 2022)
Background: Cardamine violifolia (Cv) is a kind of selenium-enriched plant which contains high levels of organic selenium (Se) such as selenocysteine and methylselenocysteine. This study was conducted to investigate the effects of this new source of Se on the growth performance, anti-oxidative capacity and meat quality in broilers compared with other frequently-used Se sources. Methods: A total of 240 broilers were allotted into 4 treatments: (1) Control group (Se free diets, CON); (2) Sodium selenite group (0.3 mg/kg Se sourced from Na2SeO3 diets, SeNa); (3) Selenium yeast group (0.3 mg/kg Se sourced from Se-Yeast diets, SeY); (4) Plant Se group (0.3 mg/kg Se sourced from Cv diets, SeCv). The whole study lasted 42 days and was divided into 2 stages (1-21 d as earlier stage and 22-42 d as later stage). Results: The results showed that the broilers fed SeCv diets had improved average daily gain and the ratio of feed to gain compared to the broilers fed SeNa and SeY diets during the earlier stage. However, there was no significant difference in growth performance of broilers fed these 3 sources of Se diets during the whole period. The broilers fed SeCv diets had improved intestinal mucosal morphology on d 21 and 42. Enhanced liver T-AOC was observed from the broilers fed SeCv diets compared with the other 2 Se sources diets on d 21. Furthermore, lower liver MDA contents were determined from the broilers fed SeCv and SeY diets compared with SeNa diets. At last, the broilers fed SeCv had increased redness in thigh muscle and decreased cooking loss in both breast and thigh muscle compared with the boilers fed SeNa diets. However, the broilers had similar meat quality between SeCv group and SeY group. Conclusion: In conclusion, these results demonstrated that SeCv was a well organic Se source for broilers.